Generation of a novel monoclonal antibody that recognizes the alpha (α)-amidated isoform of a valine residue. Issue 1 (December 2015) - Antón Palma, Benito; Leff Gelman, Philippe; Medecigo Ríos, Mayra; Calva Nieves, Juan; Acevedo Ortuño, Rodolfo; Matus Ortega, Maura; Hernández Calderón, Jorge; Hernández Miramontes, Ricardo; Flores Zamora, Anabel; Salazar Juárez, Alberto
Abstract Background Alpha (α)-amidation of peptides is a mechanism required for the conversion of prohormones into functional peptide sequences that display biological activities, receptor recognition and signal transduction on target cells. Alpha (α)-amidation occurs in almost all species and amino acids identified in nature. C-terminal valine amide neuropeptides constitute the smallest group of functional peptide compounds identified in neurosecretory structures in vertebrate and invertebrate species. Methods The α-amidated isoform of valine residue (Val-CONH2 ) was conjugated to KLH-protein carrier and used to immunize mice. Hyperimmune animals displaying high titers of valine amide antisera were used to generate stable hybridoma-secreting mAbs. Three productive hybridoma (P15A4, P17C11, and P18C5) were tested against peptides antigens containing both the C-terminal α-amidated (–CONH2 ) and free α-carboxylic acid (−COO− ) isovariant of the valine residue. Results P18C5 mAb displayed the highest specificity and selectivity against C-terminal valine amidated peptide antigens in different immunoassays. P18C5 mAb-immunoreactivity exhibited a wide distribution along the neuroaxis of the rat brain, particularly in brain areas that did not cross-match with the neuronal distribution of known valine amide neuropeptides (α-MSH, adrenorphin, secretin, UCN1-2). These brain regions varied in the relative amount of putative novel valine amide peptide immunoreactive material (nmol/μg protein) estimated through a fmol-sensitive solid-phase radioimmunoassay (RIA) raised for P18C5 mAb. Conclusions Our results demonstrate the versatility of a single mAb able to differentiate between two structural subdomains of a single amino acid. This mAb offers a wide spectrum of potential applications in research and medicine, whose uses may extend from a biological reagent (used to detect valine amidated peptide substances in fluids and tissues) to a detoxifying reagent (used to neutralize exogenous toxic amide peptide compounds) or as a specific immunoreagent in immunotherapy settings (used to reduce tumor growth and tumorigenesis) among many others.